2023
DOI: 10.15212/zoonoses-2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq Analysis of the BCG Vaccine in a Humanized Mouse Model

Abstract: Objective: This study was aimed at screening differentially expressed genes (DEGs) and exploring the potential immune mechanism induced by the Bacillus Calmette-Guerin (BCG) vaccine in a humanized mouse model. Methods: Candidate DEGs between mice vaccinated with BCG or injected with PBS were identified through transcriptomics, and their biological functions, signaling pathways, and protein interaction networks were analyzed through bioinformatics. Results: A total of 1035 DEGs were identified by transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…We have analyzed the relationship between a history of BCG vaccination and LTBI and found that there was no significant relationship between a history of BCG vaccination and latent infection, as the protective effect of BCG generally lasts for 5–10 years. Although previous studies have shown that young women living in rural areas, those living in western China, and those without a history of BCG vaccination are more likely to develop severe TB ( 26 ), the protective effect of BCG in adults is poor ( 27 , 28 ). Hence, all collective living groups (students, workers, older adults living in nursing homes, and prisoners) should receive TB screening, and personnel without a latent infection should be revaccinated with BCG.…”
Section: Discussionmentioning
confidence: 99%
“…We have analyzed the relationship between a history of BCG vaccination and LTBI and found that there was no significant relationship between a history of BCG vaccination and latent infection, as the protective effect of BCG generally lasts for 5–10 years. Although previous studies have shown that young women living in rural areas, those living in western China, and those without a history of BCG vaccination are more likely to develop severe TB ( 26 ), the protective effect of BCG in adults is poor ( 27 , 28 ). Hence, all collective living groups (students, workers, older adults living in nursing homes, and prisoners) should receive TB screening, and personnel without a latent infection should be revaccinated with BCG.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, since 2020, there has been a surge in studies focusing on TB MEVs (3,(28)(29)(30)(31)(32)(33)(34). In our previous study, we reported the method of correctly using bioinformatics and immunoinformatics tools to design TB MEVs and developed several novel MEVs based on these tools (15,17,18,20,35,36). This investigation successfully developed a novel MEV targeting TB by incorporating 13 helper T lymphocytes (HTL) epitopes, 13 cytotoxic T lymphocytes (CTL) epitopes, and 8 B-cell epitopes derived from 17 potential antigens of MTB.…”
Section: Introductionmentioning
confidence: 99%